Disease, Famine, and Death in Prisons, Concentration Camps and Forced Labor Units in Cordoba (1937-1943) - Navarro López, Francisco (Hispania Nova, 2023)
The Franco regime created an vast concentration network throughout the entire province of Cordoba, which, parallel to the prison network, imposed inhuman conditions on prisoners of war and political prisoners. Attempts to reduce and prevent the development of epidemics by Franco’s health authorities were unsuccessful due to non-existent or deficient medical assistance in detention centers. The prevalence of pediculosis and scabies, or exanthematic typhus disease that spread among those people confined in the concentration camps and the different units of forced labor worsened the poor, unsanitary and overcrowded conditions that the republican captives had to endure. If during the war the atrocities followed one another continuously, in the immediate postwar period the repression on the defeated did not cease. Panic, terror and death, victims of the most diverse misfortunes, spread through all the prisons leaving in its wake a trail of deaths that even today has not been fully quantified.